Hospice UK National Conference 2018. (2nd February 2019) - Bleakley, Tracey; Richardson, Heather; O'Leary, Shaun; Scates, Caroline; Dening, Karen Harrison; Harrison, Kerry
Foreword: Hospice UK's annual conference is the national hospice and palliative care charity's flagship event, bringing together everyone involved in leading hospice, palliative and end-of-life care for adults, children and young people. In 2018, the conference spanned two days and was held at the International Centre in Telford, Shropshire. Its theme was Transforming Palliative Care and it provided a unique forum for delegates to discuss current and forthcoming issues facing the hospice and palliative care community, and to discover new ways of thinking from outside of the sector. Packed with stimulating plenary and parallel sessions, and opportunities to network with peers and meet major providers of services and products, the conference combined high-level strategic thinking, application into practice and lessons from real-world examples. More than 800 delegates from across the hospice voluntary sector, the NHS and academia attended the conference. They included a wide cross-section of people from the hospice and palliative care sector, such as chief executives, trustees, clinical directors, nurses and doctors, as well as senior staff working in income generation, communication, operations and HR. Leaders of NHS hospices, hospitals and other care providers also attended the event.